Incorporating aluminum species in MnOx(s) coatings on water filtration media. Issue 1 (28th December 2018) - Jones, Andrew; Murayama, Mitsu; Knocke, William R.
Abstract : The manganese oxide (MnOx (s)) coatings often found on water treatment filtration media are known to effectively remove dissolved manganese from water, but little is known about the chemistry and the formation of these MnOx (s) coatings. This study evaluated the role of particulate aluminum (Al) species (specifically Al(OH)3 (am)) as a source for aluminum found in these media coatings. Bench‐scale experiments and surface analysis techniques evaluated the aluminum and manganese content of the media coatings formed under varying conditions. Particulate aluminum species were shown to be a significant source of aluminum in the MnOx (s)‐based coatings on filter media. Likewise, aluminum incorporation into the media coating did not take place without soluble manganese and free chlorine concurrently being applied to the filter media. Analysis of the MnOx (s) coating by electron microscopy showed a heterogeneous surface composed of a mix of weakly crystalline manganese oxides existing alongside amorphous Al(OH)3 (am) species.